The Effect of STH Worm Infection on the Nutritional Status of Farmers in the Agronursing Area: Literature Review - Alfid Tri Afandi; Enggal Hadi Kurniyawan; Selfi Dwi Cahyani; Wahyu Novia Fajriati; Adelia Dewi Oktaviana; Kholid Rosyidi Muhammad Nur; Dicky Endrian Kurniawan (Health and Technology Journal (HTechJ), 2023)
STH (Soil Transmitted Helmints) worm infection is a disease that often occurs in people who live in agro-industrial areas, especially in people who work as farmers. Someone often underestimates this disease, even though if this disease attacks adults, it can cause it to occur decline in health conditions and work productivity. One way to prevent worms namely by promoting a clean and healthy life. This study aimed to determine whether there was a relationship between infection and the nutritional status of farmers. This study utilized a literature review to examine further the relationship between STH worm infections and nutritional status in an agronursing environment. The method used was a narrative literature review or traditional review. The literature search was conducted through article search engines, including Google Scholar and Research Gate. The results of the 10 articles found that the nutritional status and STH infection were not significantly affected, while some articles revealed that nutritional status based on upper arm circumference had a significant association with infectious disease morbidity.